Dietary glycemic load and risk of diabetic retinopathy: a systematic review and meta-analysis - Ali, Ayub; Deepshikha; Nagar, Yogita (International Journal of Research in Medical Sciences, 2026)
Diabetic retinopathy (DR) is a leading cause of preventable blindness globally. While chronic hyperglycemia is a well-established determinant of DR, dietary carbohydrate quality reflected by glycemic index (GI) and glycemic load (GL) may independently influence microvascular damage. Objectives of the study were to evaluate published evidence examining the association between dietary GL and the prevalence or progression of DR. A PRISMA 2020-compliant systematic review was conducted. PubMed, Embase, Web of Science, and Cochrane Library were searched from inception to March 2025. Observational and interventional studies assessing dietary GI/GL and reporting DR outcomes were included. Data were narratively synthesized; where appropriate, meta-analytic methods using random-effects models were described. Fourteen studies met inclusion criteria, comprising cross-sectional and longitudinal cohort designs. Most studies reported a positive association between higher dietary glycemic load and increased DR risk or progression. Evidence suggested that diets characterized by refined carbohydrates and high glycemic load were associated with worse retinal outcomes, independent of HbA1c in several cohorts. Available evidence suggests dietary glycemic load may represent a modifiable risk factor in diabetic retinopathy. High-quality longitudinal studies and randomized dietary interventions are needed to confirm causality and inform clinical dietary recommendations.